The Shemita Effect, How a Jewish agricultural law prompted fear for Evangelical investors: Confirmation Bias and Bandwagoning in Action - Newfeld, Daria J. (Journal of Economics and Behavioral Studies, 2017)
This paper examines how Shemita, a Jewish agricultural law only applicable in Israel came to be viewed by Evangelical Christian Investors as a signal of a potential stock market crash in September, 2015 purportedly as a consequence of G-dâ€™s displeasure with the United States. In 2014 Johnathan Cahn, a popular Evangelical preacher, published â€œThe Shemita Effectâ€ which claimed that the seven year Shemita cycle mirrored stock market patterns over the last 50 years and suggested an impending crash. This theory was quickly taken up by conservative Christian Evangelical media and at least one man was convinced enough to start an entire investment company based on it despite the fact that it is easily disproven using basic statistical analysis of freely available data. This bizarre incident illustrates confirmation bias and bandwagoning effects in action, amplified with religious fervor.